The Roots and Forming of German Nationalism Ideology – Part II: From 1815 (Congress of Vienna) to 1914 - Maciąg, Anna (Sensus Historiae, 2019)
The work considers the development of the idea of German nationalism from the the turn of the 18th century to the outbreak of the First World War. On the one hand, the political and social situation of the German territories in 19th Century (the politics of Frederick the Great, the German Enlightenment, state crisis during the Napoleonic wars, the student movement and the rise of the corporation movement, the unification of the German lands, German expansionist policy before WWI and the concept of Mitteleuropa) had an impact on this development. On the other hand, writings of popular representatives of the prevailing political and ideological currents cannot be ignored. The work is divided into two parts. The second part presents the process of shaping of the idea of nationalism idea from 1815 (Congress of Vienna) to 1914. The impact of conservative and liberal thinking on emerging nationalism and the implications of works of Carl Ludwig von Haller, Heinrich Hermann Riemann, Joan Georg August Wirth, Wilhelm Jordan, Friedrich Ratzel and Alfred Weber are also discussed.